1k-(-75)=-95

Simple and best practice solution for 1k-(-75)=-95 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1k-(-75)=-95 equation:


Simplifying
1k + -1(-75) = -95

Multiply -1 * -75
1k + 75 = -95

Reorder the terms:
75 + 1k = -95

Solving
75 + 1k = -95

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-75' to each side of the equation.
75 + -75 + 1k = -95 + -75

Combine like terms: 75 + -75 = 0
0 + 1k = -95 + -75
1k = -95 + -75

Combine like terms: -95 + -75 = -170
1k = -170

Divide each side by '1'.
k = -170

Simplifying
k = -170

See similar equations:

| 3(x+4)=3x+2 | | X/7=81 | | 6(2l+3)=90 | | x^2-3x-4=14 | | x^6/2 | | 5/8=4x | | -x+11=13 | | -4p+5=-4 | | 2x-5/x-4=0 | | 2x-5)/x-4=0 | | an=4-3/n | | 4x-20-4x= | | 5x^2+x-50=0 | | -2(1-8b)-8b=8b+4 | | C-32=73 | | 2cosx^2+5cosx-2=0 | | 5xy^2-3xy=4 | | 3x+-2x+4=10 | | n*5=73 | | k-6(-k-6)=-3(-k-8) | | -2(1+6n)=7(2-4n) | | f(x)=x^4-81 | | 2(7+3r)=1(r+7) | | .4x+4.5=.8x+1.3 | | -14x=-12(x+1) | | -4(n+1)-4n=-6+2(-6n+3) | | 3(6)+y=10 | | 14*n= | | -158-3x=6x+94 | | x-2/5=2x | | 6+1.2x=36 | | -6(x-3)=10(x+5) |

Equations solver categories